2014
DOI: 10.1680/geng.13.00128
|View full text |Cite
|
Sign up to set email alerts
|

Construction techniques for bored piling in sand using polymer fluids

Abstract: This paper is concerned with the use of polymer fluids for the construction of bored piles in silty fine sand, a situation which has been found to significantly increase the risk of ‘soft toes' and concrete contamination due to the settling of the suspended soil particles in the fluid. To illustrate how these problems can be avoided by adopting a simple fluid-testing regime and improved construction practice, this paper presents a case history of polymer use at a site in Glasgow where the ground conditions con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Polymer fluids have been found to offer many benefits such as smaller site footprint, ease of fluid mixing, and better concrete-sand interface resistance (Lennon et al 2006;Lam et al 2014a). However, since polymer fluids are very different from their bentonite counterparts both physically and chemically, their methods of use are also very different (Jefferis and Lam 2013;Lam et al 2014b) and workmanship issues have arisen on some projects in the past (Berkovitz and Long 1995;Institution of Civil Engineers 2007). Therefore, despite the potential benefits many practicing engineers still remain wary of polymer use (Wheeler 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Polymer fluids have been found to offer many benefits such as smaller site footprint, ease of fluid mixing, and better concrete-sand interface resistance (Lennon et al 2006;Lam et al 2014a). However, since polymer fluids are very different from their bentonite counterparts both physically and chemically, their methods of use are also very different (Jefferis and Lam 2013;Lam et al 2014b) and workmanship issues have arisen on some projects in the past (Berkovitz and Long 1995;Institution of Civil Engineers 2007). Therefore, despite the potential benefits many practicing engineers still remain wary of polymer use (Wheeler 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were verified by Lam et al [ 9 ] and Lam [ 10 ], who observed that piles formed with polymer fluid significantly outperformed piles supported by bentonite fluid, and little difference was found between piles drilled within 7.5 h and 26 h. Bustamante et al [ 11 ] investigated piles constructed with polymer fluid in pyroclastic soil consisting of pumice and lapilli, and they concluded that polymer fluid showed no adverse effect on pile shaft resistance in the pyroclastic soils. Similar successful cases of polymer fluids as a pile bore stabilizer can also be found in sand [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 72%
“…The fluid flow rate is dependent on PSF shear viscosity [35]. Because soil particles settling velocity in fluid depends on viscosity and elasticity, therefore, reasonable amount of detritus accumulation takes place at the basal part of excavation or at the upper (top) part of fresh concretion as it is termied into the hole [36][37]. Sedimentation of soil particles occurs in creeping flow regime (Reynolds number, R < 1) without influencing by fluid elasticity in agreeing with [38] who also reported no effect of fluid elasticity on the particle drag when Deborah number (De) < 0.1.…”
Section: Rheological Characteristics Of Phpas Polymer Support Fluids ...mentioning
confidence: 99%